2019
DOI: 10.3846/btp.2019.43
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Finance and Economic Growth: Evidence From Nigeria

Abstract: The study performed an in-depth examination of the impact of guaranteed agricultural finance to oil palm, cocoa, groundnuts, fishery, poultry, cattle, roots, and tubers on the real gross domestic product of the country. Time series data was sourced from the Central Bank of Nigeria statistical bulletin of various issues. The data sets covered thirty-seven (37) years spanning from 1981 to 2017. The study used Autoregressive Distributed Lag (ARDL) model for its analysis. However, prior estimation and due to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…Majority of the respondents 39.13% belonged to the age group of between (31-40) years, 30% of the respondents were aged between (41-50) years, 20% haviing less than 30 years while 10.87% were above 50 years (table 3). Similar results were revealed by a study conducted by [18] and [16]. Based on their findings, majority of rural farmers were in the middle class age hence considered as active working age category.…”
Section: Analytical Techniquessupporting
confidence: 88%
“…Majority of the respondents 39.13% belonged to the age group of between (31-40) years, 30% of the respondents were aged between (41-50) years, 20% haviing less than 30 years while 10.87% were above 50 years (table 3). Similar results were revealed by a study conducted by [18] and [16]. Based on their findings, majority of rural farmers were in the middle class age hence considered as active working age category.…”
Section: Analytical Techniquessupporting
confidence: 88%
“…This result discloses that government investment on agriculture is too inconsequential to guarantee food security at the moment in Nigeria. This result agrees with the findings of Okunlola et al (2019) whose study revealed that agricultural financing in Nigeria has not affected economic growth significantly.…”
Section: Trend Analysissupporting
confidence: 92%
“…In the same manner human capital development or formal education and knowledge of farmers, marital status and extension services were the significant factors that influence the growers' productivity after embracing a maintenance system of cultivation. Okunlola et al (2019) researched on the effect of agricultural financing on economic growth of Nigeria using Autoregressive Distributed Lag (ARDL) technique and data from 1981 to 2017. The study revealed that expenditure on agriculture was statistically insignificant and could not positively influence economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The stepwise regression method was proposed to test the interactions between variables, highlighting this regression analysis method [91]. The impact of agricultural output on economic growth was explored using the dynamics of the different technical approaches that stepwise regression can provide [92]. Additionally, the interaction effect between economic growth and environmental pollution in Wuhan in China was studied using the stepwise regression method by selecting critical indicators of economic growth and environmental pollution [93].…”
Section: Emprical Methodsmentioning
confidence: 99%